Three Aspects of the Phenomenon of Science: In Search for Unity among Sociologists - N. G. Popova; E. V. Biricheva; T. A. Beavitt (Образование и наука)
Introduction. In today’s globalising world, science acquires a crucial importance: integrating humanity within the framework of solving global problems, it becomes one of the leading factors in social development, facilitating work and diversifying leisure time, as well as serving as an instrument of transformations in the political sphere. Undoubtedly, the social aspects of contemporary science are capturing the attention of a huge number of researchers. However, it is not clear that all areas of the sociology of science treat the object of their study in the same way.Aim. A lack of reflection on the unity or otherwise in the understanding of the essence of science in the various fields of sociological research makes it difficult to compare different theories of the institutional, cultural, social and communicative contexts of scientific development. An urgent methodological task therefore consists in developing an understanding of the various definitions of the concept of “science” used in the framework of contemporary sociological analysis of this phenomenon.Results and scientific novelty. In this paper, two dominant sociological views on science – as an experimental-mathematical approach to cognising the world and as a system of representations in general – are compared. We conclude that while researchers studying institutional aspects of science tend to interpret it in terms of the “heritage” of post-Enlightenment European rationalism, constructionist and communicatively-oriented researchers tend to approach science as the system of knowledge and cognition that is formed in any human society, having its own specific sociocultural features in each respective case. While each of these two approaches undoubtedly has its own methodological potential, in order to provide such a diverse field of studies with a common ground, it would be necessary to balance them with a third aspect. We argue that this balancing role, since both common for all mankind and unique for every culture, could be played by Heidegger’s conceptualisation of science as “the theory of the real”.Practical significance. In order to avoid a pluralism of incompatible theories, it is important to continually pose the question “what is the object of study when conducting a sociological study of various scientific phenomena?” – as well as to understand the “limits of applicability” of the particular interpretation of science on which basis sociological analysis proceeds.